2007
DOI: 10.1103/physrevb.76.205319
|View full text |Cite
|
Sign up to set email alerts
|

Phonon-plasmon coupling in electron surface accumulation layers in InN nanocolumns

Abstract: Raman measurements in high quality InN nanocolumns display a coupled LO phonon-plasmon mode together with uncoupled phonons. The coupled mode is attributed to the spontaneous accumulation of electrons on the lateral surfaces of the nanocolumns. For increasing growth temperature, the electron density decreases as the growth rate increases. The present results indicate that electron accumulation layers do not only form on polar surfaces of InN but also occur on nonpolar ones. According to recent calculations, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 32 publications
4
54
0
Order By: Relevance
“…6, N D + and N ss + values in Table III support the idea of two distinctive regions in the NWs, and agree with the coexistence of plasma coupled and uncoupled LO modes in the Raman spectra of these nanostructures. 20,21 Other aspects of the optical response also reinforce the proposed picture. For instance, the existence of a Stokes shift which increased in magnitude with the absorption edge energy can be understood from the fact that different processes lead to emission and absorption.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…6, N D + and N ss + values in Table III support the idea of two distinctive regions in the NWs, and agree with the coexistence of plasma coupled and uncoupled LO modes in the Raman spectra of these nanostructures. 20,21 Other aspects of the optical response also reinforce the proposed picture. For instance, the existence of a Stokes shift which increased in magnitude with the absorption edge energy can be understood from the fact that different processes lead to emission and absorption.…”
Section: Discussionsupporting
confidence: 65%
“…[17][18][19] On the other hand, a careful investigation of the photoluminescence ͑PL͒ peaks of InN NWs provided indirect evidences of a surface layer with degenerate electrons which is optically inactive. 20 Finally, the coexistence of a plasmon-coupled mode and longitudinal optical modes in the Raman spectra 20,21 indicated that while the NW core remains intrinsic, high electron densities are present at their lateral walls. These experimental results point out a complex interplay between the NW surface and core regions, where the free-electron densities should differ considerably.…”
Section: Introductionmentioning
confidence: 99%
“…However, contrary to the LO mode, the TO intensity decreases back again for large pitch distances (larger than 1200 nm). In wurtzite material, it has been observed by Raman scattering that light coupling enables light entering the nanowires to a considerable extent through their side facets even for normal incidence and small bandgap material [73,74]. Because the Raman signal is directly related to the electric field direction through the symmetry of the vibrational mode in question, the change in the field direction at the nanoscale can completely modify the Raman selection rules for different modes from the macroscopic point of view.…”
Section: Raman Scattering In Standing Inas Nanowire Arraysmentioning
confidence: 99%
“…It is also interesting to look at the surface electron properties since the ubiquitous surface electron accumulation has been so far reported to occur at all InN surfaces: WZ polar, nonpolar and semipolar, as well as at the ZB InN surface [23,[26][27][28]. However, for the ZB InN, no information on the purity of the polymorph was given [27].…”
Section: E Phonon and Free-charge Carrier Propertiesmentioning
confidence: 99%
“…The InN layer is considered to be composed of bulk region and surface layer with different free electron concentration according to experimental findings of electron accumulation occurring at InN surfaces [23,[26][27][28]. The light propagation within the entire sample stack is calculated by applying a 4 × 4 matrix algorithm for multilayer systems assuming plane parallel interfaces.…”
Section: Ellipsometry Model Dielectric Function and Data Analysismentioning
confidence: 99%